Effect of combining platelet-rich fibrin with synthetic bone graft on the healing of intrabony defects after apicectomy in dogs with periapical pathosis - Doaa G Basta; Ashraf M Abu-Seida; Kariem M El-Batouty; Hossam M Tawfik (Saudi Endodontic Journal, 2021)
Introduction: An apicectomy is traditionally a surgical endodontic procedure that deals with the local excision of the root tip and periapical pathosis of failed conventional root canal treatment. The proper healing of the intrabony defects plays a crucial role in the success of endodontic surgery. This study evaluates the role of platelet rich fibrin (PRF) in conjunction with synthetic bone graft on the healing of intrabony defects after apicectomy in dogs with induced periapical lesion. Materials and Methods: Induced periapical pathosis and root canal obturation were carried out in 36 mandibular premolar dogs, teeth, then treated with either apicectomy (Group I) or apicectomy followed by application of PRF and synthetic bone graft (Group II). The periapical healing of both groups was evaluated by radiography and histopathology after 1 month (subgroup A) and 3 months (subgroup B). The periapical bone density, percentage of difference in radiodensity, inflammatory cell count, and percentage of new bone formation were measured. The quantitative data of both groups were statistically analyzed. The P < 0.05 was considered statistically significant. Results: There were significant differences between both groups in periapical radiodensity, percentage of difference in radiodensity, mean inflammatory cell count, and percentage of new bone formation in both subgroups (P < 0.05). In contrast to Group I, Group II exhibited high significant differences between both subgroups in the mean radiodensity, percentage of difference in radiodensity, and new bone formation (P < 0.001). Conclusions: Using of PRF in conjuction with the synthetic bone graft enhances the healing of periapical intrabony defects after apicectomy in dogs' teeth.